Cultura, linguagem e o desenvolvimento das crianças surdas - Santana, Sirlândia Souza (2009)
This work aims to investigate the implications of language restriction on human formation, pointing the necessity of creating a language policy for the deaf from early childhood, as a way to ensure effective social participation of deaf people in different cultural spaces: family, community and school. Takes as empirical focus the development of cultural processes of deaf adolescents in the city of Itabuna-BA. To do so, presents a reflection about language as the main cultural tool for human growth, with the theoretical framework the culture conceptions of Geertz; human development of Vygotsky; the language of Bakhtin; the concept of deafness of Sacks and Sá, and the study of Brazilian Sign Language Brazil, defended by Tables & Karnopp, for the possibility of understanding the concept of human development that these theoretical positions present. The research presents an approach preferably qualitative, though make use of quantitative data in a complementary manner. The relevance of the research is to develop, in a systematic way, the knowledge about deafness from the analysis of the language absence implications in early childhood and its consequences for human development. It is also intended to contribute for the social development practices that recognize the necessity of implementing a linguistic policy for deaf children from 0 to 5 years. This study combines to several others, confirming the understanding of the deafness experience as formative experience of a specific cultural universe. Having the Brazilian Sign Language (LIBRAS) as fundamental element of mediation between the language and the humane development